Auxin: an emerging regulator of tuber and storage root development - Kondhare, Kirtikumar R.; Patil, Aruna B.; Giri, Ashok P. (Plant Science, 2021)
Many tuber and storage root crops owing to their high nutritional values offer high potential to overcome food security issues. The lack of information regarding molecular mechanisms that govern belowground storage organ development (except a tuber crop, potato) has limited the application of biotechnological strategies for improving storage crop yield. Phytohormones like gibberellin and cytokinin are known to play a crucial role in governing potato tuber development. Another phytohormone, auxin has been shown to induce tuber initiation and growth, and its crosstalk with gibberellin and strigolactone in a belowground modified stem (stolon) contributes to the overall potato tuber yield. In this review, we describe the crucial role of auxin biology in development of potato tubers. Considering the emerging reports from commercially important storage root crops (sweet potato, cassava, carrot, sugar beet and radish), we propose the function of auxin and related gene regulatory network in storage root development. The pattern of auxin content of stolon during various stages of potato tuber formation appears to be consistent with its level in various developmental stages of storage roots. We have also put-forward the potential of three-way interaction between auxin, strigolactone and mycorrhizal fungi in tuber and storage root development. Overall, we propose that auxin gene regulatory network and its crosstalk with other phytohormones in stolons/roots could govern belowground tuber and storage root development.
Keywords: Auxin; Potato; Storage root; Sweet potato; Tuber

Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites